Gender Differences in the Educational and Occupational Expectations of Rural Ohio Youth - Kerry S. Odell (Journal of Research in Rural Education, 1988)
Females (N =248) and males (N =243), in grades IOand 12atfour rural Ohio high schools, geographically representative of the state, were surveyed to ascertain their educational and occupational expectations. The young women showed significantly higher educational and occupational expectations than did the males. Areas of anticipated college study and occupational expectations were shown to be sex stereotypic. Results are presented with respect to previous findings and current conditions in rural schools.